Employer sanctions: A policy with a pitfall? - Oded Stark; Marcin Jakubek (University of Tübingen, Faculty of Economics and Social Sciences, 2021)
This chapter investigates the impact of the imposition of sanctions for employing illegal migrants on the welfare of native laborers. In response to such sanctions, managers in a firm may be reassigned from the supervision of production to the verification of the legality of the firm's labor force. The chapter analyzes three different conditions of the host country's labor market: full employment, voluntary unemployment, and minimal wage in combination with involuntary unemployment. It is shown that when the sanctions are steep enough, a profit-maximizing firm will assign managers to verification, which impedes the firm's productivity. The impact on the wages and / or employment of the native laborers depends on the efficiency of the verification technology, namely on the percentage of the 'filtered out' illegal laborers in relation to the fraction of reassigned managers. If this efficiency is not high enough, the sanctions bring in their wake consequences that fly in the face of the very aim of their introduction: the welfare of the native laborers will take a beating.
urn:nbn:de:bsz:21-dspace-1165536; hdl:10900/116553
Keywords: D21; I38; J21; J61; K31; L51; 330; Employer sanctions; Illegal migrant laborers; Welfare of native laborers